Pengaruh Financial Performance terhadap Nilai Perusahaan Industri Pertambangan yang Terdaftar di Bursa Efek Indonesia - Maria Junianta (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2022)
This study aims to determine how much the influence of financial performance (Current Ratio, Leverage, Working Capital Turnover, and Return On Assets on corporate value (Price to Book value). The data analysis models used in this sudy are descriptive statistical analysis and inference. The population in this study is mining companies listed on the Indonesia Stock Exchange during the period of 2016 to 2020. The sample is chosen by using purposive sampling, and there are 23 companies in which the sample collection of companies with criteria of having financial reports during the years of the study period. The result shows that the variables of CR, WCT, and ROA have significant positive effect corporate value. The result also shows that variables of LEV have a significant negative effect on corporate value.